2007
DOI: 10.1111/j.1745-4573.2007.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Monoxide and High Oxygen Modified Atmosphere Packaging (Map) on Quality Characteristics of Beef Strip Steaks

Abstract: Carbon monoxide (CO), recently approved as a modified atmosphere packaging (MAP) gas, has the potential to extend color shelf life in case‐ready beef. The objective was to determine how CO versus traditional high oxygen MAP treatments affect beef quality. Strip loins were enhanced with a commercial phosphate–salt solution. Steaks were cut, packaged in atmospheres containing either 0.4% CO/30% CO2/69.6% N2 (HiOx) or 80% O2/20% CO2 (HiOx), aged in the dark for 12 and 26 days, and placed in a lighted retail displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Few studies have reported long periods of visual color evaluation. Our results were not in accordance with those of Stetzer and others (2007), who reported that phosphate‐enhanced steaks (containing 0.4% phosphate, 0.3% salt, and 0.1% natural flavoring) in high‐oxygen MAP (80% O 2 /20% CO 2 ) were moderately red after 14 d and less red after 28 d of storage at 4 °C under fluorescent lights. In the current study, steaks from both treatments started out on day 0 retail display (day 5 total) cherry red.…”
Section: Resultscontrasting
confidence: 99%
“…Few studies have reported long periods of visual color evaluation. Our results were not in accordance with those of Stetzer and others (2007), who reported that phosphate‐enhanced steaks (containing 0.4% phosphate, 0.3% salt, and 0.1% natural flavoring) in high‐oxygen MAP (80% O 2 /20% CO 2 ) were moderately red after 14 d and less red after 28 d of storage at 4 °C under fluorescent lights. In the current study, steaks from both treatments started out on day 0 retail display (day 5 total) cherry red.…”
Section: Resultscontrasting
confidence: 99%
“…Salt and SP act in concert to alter protein solubility that in turn improves the ability of protein to hold water (Bendall 1954; Offer and Trinick 1983; Trout and Schmidt 1986; Lawrence and others 2004). Other benefits that are sometimes realized include increased tenderness and improved flavor (Sheard and others 1999; Robbins and others 2003; Wicklund and others 2005; Stetzer and others 2007, 2008) and reduced lipid oxidation (Lamkey and others 1986; Ladikos and Lougovois 1990; Craig and others 1991; Pohlman and others 2002a, 2002b; Duong and others 2008). Challenges include off‐flavors such as alkaline or “soapy” when phosphate levels are high (Vote and others 2000) and reduced color stability or darker color (Lawrence and others 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Beef packaged 0.1% and 0.25% CO atmospheres had color stability similar to that of beef packaged in HiOx‐MAP, but beef packaged in ≥0.5% CO had more desirable color stability than beef packaged in HiOx‐MAP (Luño and others 2000). The color stability of beef strip steaks packaged in a 0.4% CO anoxic atmosphere is greater than the color stability of beef strip steaks packaged in HiOx (Stetzer and others 2007). Incorporating CO into meat injection enhancement solutions did not stabilize color (Hamling and others 2008).…”
Section: Introductionmentioning
confidence: 91%